2017
DOI: 10.1055/s-0036-1597284
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Extracellular DNA: Cause or Consequence of Thrombosis?

Abstract: Thrombosis leads to ischemic organ damage in cardiovascular and thromboembolic diseases. Neutrophils promote thrombosis in vitro and in vivo by releasing neutrophil extracellular traps (NETs). NETs are composed of DNA filaments coated with histones and neutrophil enzymes such as myeloperoxidase (MPO). Circulating extracellular DNA (ceDNA) is widely used as a surrogate marker to monitor NET formation in thrombosis. This narrative review summarizes the association of ceDNA with human thrombosis. Levels of ceDNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 111 publications
(210 reference statements)
2
45
0
Order By: Relevance
“…It has been recommended to study procoagulant activity of cfDNA with the use of different DNA‐isolation techniques . Our results suggest that the high levels of circulating cfDNA during liver transplantation contribute to in vivo activation of coagulation, which is in line with clinical studies that have described the association between elevated plasma levels of cfDNA (and nucleosomes) and thrombotic diseases …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It has been recommended to study procoagulant activity of cfDNA with the use of different DNA‐isolation techniques . Our results suggest that the high levels of circulating cfDNA during liver transplantation contribute to in vivo activation of coagulation, which is in line with clinical studies that have described the association between elevated plasma levels of cfDNA (and nucleosomes) and thrombotic diseases …”
Section: Discussionsupporting
confidence: 87%
“…These constituents together form a weblike structure, referred to as neutrophil extracellular traps (NETs), which was first described as a mechanism of pathogen entrapment and clearance . Clinical studies have shown that increased plasma levels of cfDNA and other (more specific) markers for NETs are found in patients with thrombotic diseases, such as deep vein thrombosis, myocardial infarction, and stroke, and it has been suggested that NETs form a risk factor for development of thrombotic disease . Experimental animal models have established that cfDNA and NETs are important contributors to the formation of thrombi .…”
mentioning
confidence: 99%
“…NET primarily identified, produced by neutrophils to kill microorganisms and to defend against pathogens, are demonstrated to be formed also during inflammatory events, as for example, in cystic fibrosis, thrombosis, and chronic obstructive pulmonary disease . In the last years, the list of diseases in which these neutrophil products are demonstrated to be involved was certainly increased and a key role of NET in non‐infective diseases was recently outlined .…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The first, representing the contribution from Jiménez-Alcázar et al, 7 is on the topic of circulating extracellular DNA (ceDNA), and poses the question of whether this is the cause or consequence of thrombosis? As is well known to our readers, thrombosis leads to ischemic organ damage, and potentially arises in many disease processes.…”
mentioning
confidence: 99%